Metaphors in selected Blackpink’s song lyrics - Bernadetta, Monica Pricillia; Linuwih, Endar Rachmawaty; Kurniawan, Yulius (Journal of English Language and Pedagogy (JELPA), 2023)
The primary goal of this research was to examine metaphors in selected Blackpink song lyrics. The study's objectives are to identify the types of metaphors syntactically based on Abdul Wahab (1986) and to analyse the metaphorical meanings of selected Blackpink song lyrics using Lakoff and Johnson's source and target (1980). A descriptive-qualitative approach is used in this study. The metaphors used in Blackpink's song lyrics were the data. The researcher applies Abdul Wahab's theory of syntactical types of metaphor to the identified data and analyses it using Lakoff and Johnson's concept of source and target in metaphor. Subjective nominative metaphor, objective nominative metaphor, predicative metaphor, and sentence metaphor were the four types of metaphor used in five selected Blackpink song lyrics. The writer finds that the phrase metaphor is the type of metaphor most commonly used in Blackpink's songs, followed by the objective metaphor of the predicative metaphor and subjective metaphor. Each of the types of metaphors collected in the following study contains abstract terms with real meanings.